2022
DOI: 10.3390/brainsci12020287
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Resting State Attentional Network Connectivity in Adolescent and Young Adult Cannabis Users following Two-Weeks of Monitored Abstinence

Abstract: Background. Numerous neuropsychological studies have shown that cannabis use during adolescence and young adulthood led to deficits in sustained and selective attention. However, few studies have examined functional connectivity in attentional networks among young cannabis users, nor have characterized relationships with cannabis use patterns following abstinence. Methods. Differences in resting state functional connectivity (RSFC) within the dorsal (DAN) and ventral (VAN) attention networks were examined in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Comparisons are hindered by few studies and samples limited to adolescents and young adults. A study following adolescent and young adults who were regular cannabis users revealed abnormal connectivity within the dorsal and attentional network, even after two weeks of monitored abstinence ( Harris et al, 2022 ). Another study in a sample of adults between the ages of 16–26 years who were regular cannabis users, revealed weaker connectivity between the left posterior cingulate cortex and various DMN nodes when compared to a matched group of non-cannabis users ( Ritchay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons are hindered by few studies and samples limited to adolescents and young adults. A study following adolescent and young adults who were regular cannabis users revealed abnormal connectivity within the dorsal and attentional network, even after two weeks of monitored abstinence ( Harris et al, 2022 ). Another study in a sample of adults between the ages of 16–26 years who were regular cannabis users, revealed weaker connectivity between the left posterior cingulate cortex and various DMN nodes when compared to a matched group of non-cannabis users ( Ritchay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in other parts of the brain are more variable and depend on the type of construct that is being examined. Comparing individuals with cannabis user disorder relative to comparison individuals, researchers found lower resting-state functional connectivity within the dorsal attention network, which was associated with more severe cannabis use measures, including increased lifetime cannabis use, shorter length of abstinence and more severe cannabis use disorder symptoms [8]. On the one hand, in participants with heroin use disorder, there appears to be a marked decrease in resting-state functional connectivity between interhemispheric dorsolateral prefrontal cortex [9].…”
Section: Case-control Studiesmentioning
confidence: 99%